Pengaruh Latihan Push Up dan Tricep Dips Terhadap Peningkatan Kekuatan Otot Lengan Atlet Bolavoli Putra Klub Perdana Wonosobo - Falih Akmal; Agung Wahyudi (Indonesian Journal for Physical Education and Sport, 2024)
This research aims to determine the effect of push up and tricep dips training on increasing arm muscle strength as well as the difference in the influence of push up and tricep dips training on increasing arm muscle strength of male volleyball athletes at the Perdana Wonosobo club. The method used is an experiment with a "two groups pretest posttest design" pattern. The sample in this study consisted of 14 athletes with the sampling technique used was total sampling. The tests carried out were pretest and posttest pull and push dynamometer. The data analysis technique uses a paired sample test with the help of SPSS version 25. The results of the research show that (1) There is an influence of push up training on athlete's arm muscle strength with tcount 12.010 > ttable 2.447, (2) There is an influence of tricep dips training on arm muscle strength athlete with tcount 9.242 > ttable 2.447, (3) There is no significant difference in effect between push ups and tricep dips training. This is based on the data obtained tcount 0.082 < ttable 1.782 with a significance level of 0.05 in the independent sample test. This proves that there is an effect of push up and tricep dips training on increasing arm muscle strength but there is no significant difference in improvement between the two exercises.